Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(A=\frac{10^8+2}{10^8-1}=\frac{10^8-1+3}{10^8-1}=1+\frac{3}{10^8-1}\)
\(B=\frac{10^8}{10^8-3}=\frac{10^8-3+3}{10^8-3}=1+\frac{3}{10^8-3}\)
Nhận thầy 108 - 1 > 108 - 3
=> \(\frac{3}{10^8-1}< \frac{3}{10^8-3}\)
=> \(1+\frac{3}{10^8-1}< \frac{3}{10^8-3}+1\)
=> A < B
b) 17C = \(\frac{17\left(17^{203}+1\right)}{17^{204}+1}=\frac{17^{204}+1+16}{17^{204}+1}=1+\frac{16}{17^{204}+1}\)
17D = \(\frac{17\left(17^{202}+1\right)}{17^{203}+1}=\frac{17^{203}+1+16}{17^{203}+1}=1+\frac{16}{17^{203}+1}\)
Nhận thầy 17203 + 1 < 17204 + 1
=> \(\frac{16}{17^{203}+1}>\frac{16}{17^{204}+1}\)
=> \(\frac{16}{17^{203}+1}+1>\frac{16}{17^{204}+1}+1\Rightarrow17C>17D\Rightarrow C>D\)
1715 và 259
ta có:
1715>1615 ; 1615= (24)15=260
Vì 260> 259=>1615>259
=>1715>259
a)3200=(32)100=9100
2300=(23)100=8100
vì 9>8 nên 9100>8100
hay 3200>2300
b)\(A=\frac{121212}{171717}+\frac{2}{17}-\frac{404}{1717}=\frac{12.10101}{17.10101}+\frac{2}{17}-\frac{4.101}{17.101}=\frac{12}{17}+\frac{2}{17}-\frac{4}{17}\)
\(=\frac{10}{17}=B\)
Vậy A=B
a) Ta có: 3200 = ( 32 )100 = 9100
2300 = ( 23 )100 = 8100
Vì 9 > 8 nên 9100 > 8100.
Vậy 3200 > 2300
b) \(A=\frac{121212}{171717}+\frac{2}{17}-\frac{404}{1717}=\frac{12}{17}+\frac{2}{17}-\frac{4}{17}=\frac{12+2-4}{17}=\frac{10}{17}=B\)
Vậy A = B
a) 2018 + (– 3) < 2018
b) (– 105) + 5 > (– 105)
c) (– 59) + (– 10) < (–59)
\(A=\frac{10^{17}+5}{10^{17}-8}=\frac{10^{17}-8+13}{10^{17}-8}=\frac{10^{17}-8}{10^{17}-8}+\frac{13}{10^{17}-8}=1+\frac{13}{10^{17}-8}\)
\(B=\frac{10^{17}}{10^{17}-3}=\frac{10^{17}-3+13}{10^{17}-3}=\frac{10^{17}-3}{10^{17}-3}+\frac{13}{10^{17}-3}=1+\frac{13}{10^{17}-3}\)
Nhận xét: \(10^{17}-8<10^{17}-3\Rightarrow\frac{13}{10^{17}-8}>\frac{13}{10^{17}-3}\Rightarrow1+\frac{13}{10^{17}-8}>1+\frac{13}{10^{17}-3}\Rightarrow A>B\)
\(A=\frac{10^{17}+5}{10^{17}-8}=\frac{10^{17}-8+13}{10^{17}-8}=\frac{10^{17}-8}{10^{17}-8}+\frac{13}{10^{17}-8}=2+\frac{3}{10^{17}-8}\)
\(B=\frac{10^{17}}{10^{17}-3}=\frac{10^{17}-3+3}{10^{17}-3}=\frac{10^{17}-3}{10^{17}-3}+\frac{3}{10^{17}-3}=1+\frac{3}{10^{17}-3}\)
Do \(2+\frac{3}{10^{17}-8}>1+\frac{3}{10^{17}-3}\)n\(A>B\)